Answer:
the inverse of a function is the exact opposite
Step-by-step explanation:
Answer:
Step-by-step explanation:
I think you meant y = -2x + 5.
x y = -2x + 5
0 5
1 -2(1) + 5 = 3
2 -2(2) + 5 = 1
Note that every time you increase x by 1, y decreases by 2.
Answer:
I believe its (- 2, 2 )
Step-by-step explanation:
Assuming the dilatation is centred at the origin, then multiply the coordinates of B by the scale factor 2, that is
B(- 1, 1 ) → B'(2(- 1), 2(1) ) → B'(- 2, 2 )
Step-by-step explanation:
use the steps of simultaneous
elimination steps